Heterogeneous photocatalysis and an anaerobic biological process for leachate treatment (2022)
The research used a coupling heterogeneous photocatalysis (TiO2-UVsolar) and an anaerobic biological process (Specific Methanogenic Activity Test) to study the treatment of leachate from a landfill in Norte de Santander (Colombia). It developed photocatalysis in a Composite Parabolic Collector (CPC), H2O2 as oxidation assistant, and the combination of different TiO2 levels and pH modeled with a factorial design 32. In the biological test, for a maximum load of 4,500 mg. L-1 of Chemical Oxygen Demand (COD) leachate, 2.0 g. L-1 of Volatile Suspended Solids (VSS) inoculum, and a hydraulic retention time of 23 days, there were no significant COD removal percentages, evidencing the recalcitrant character of these leachates. In the Advanced Oxidation Process (AOP) there was mineralization in terms of DOC of 57%, which evidences the capacity of the process to support the pollutant load of the leachate. The combined process (AOP-Biological) allows additional mineralization in terms of DOC of 21% in the biological process, for a total contribution of the coupling of 78%, which shows the capacity of the AOP to convert toxic wastewater into one with characteristics more suitable for its subsequent degradation in anaerobic biological reactors.